Intellectual property text and essential cases - Reynolds, Rocque; Stoianoff, Natalie (The Federation Press, 2008)
Intellectual Property: Text and essential cases takes the reader to the forefront of this dynamic area of law. As in previous editions it provides a comprehensive, in-depth and engaging exposition of the principles of Intellectual Property Law and selected case extracts that illustrate the law's evolution and challenges. It covers Copyright, Moral Rights, Performers Protection, Patents, Trade Marks, Passing Off and related actions, Designs, Plant Breeder's Rights, Circuit Layouts and Confidential Information. The book includes extracts from the most important cases in the field as well as helpful tables to guide the reader through the legislation